Investigation for bodies in moving frame of reference - Xavier, Briant Benjamin (Nanyang Technological University, 2023)
The Galilean invariance assumption is commonly used in Computational Fluid Dynamics (CFD). It states that the forces produced on a stationary body in moving flow is equal to the forces produced on a moving body in stationary flow. This study aims to investigate the accuracy of this assumption for both 2 dimensional (2D) and 3 dimensional cases (3D).